Diretrizes urbanísticas e ambientais para a expansão urbana de Uberlândia (MG) sobre áreas de proteção de mananciais: análise e propostas de preservação - Silva, Adriana Maria da (2023)
Urbanization over areas of water sources can contribute significantly to water scarcity, especially in regions where demand for water is high. This is because human occupation over these areas can directly affect the quality and quantity of water available for public supply. With intense soil impermeability, which prevents water infiltration and recharge of underground aquifers, the availability of water in rivers and lakes is affected. Additionally, urbanization can lead to water pollution through sewage and solid waste discharge, making the water unsuitable for human consumption and public supply. Protecting water sources in Brazil faces significant challenges in containing urban expansion, especially in scenarios where resources are scarce and there is high demand for low-income housing. In other cases, the power and influence of real estate speculation can be seen in land use planning. To address these pressures and the compromise of water resources in strategic areas of municipalities, it is important that urban planning is based on knowledge of the environmental framework of the territory, an understanding of the phenomena that result in environmental degradation, and the determination of specific regulations based on preservation. The city of Uberlândia (MG) has seen its population grow over the years, becoming the largest city in the interior of Minas Gerais, and consequently experiencing urban growth. In its macro-zoning, urban expansion overlaps with its water source protection area, without any reservation regarding the established criteria for occupation throughout the urban expansion zone. In the face of this challenge, this study projected occupation scenarios for the area through a vulnerability diagnosis of soil loss, conflicts with the current land use, and projection of possible urbanization. It also established the profile of surface runoff in the area through the CN Method, comparing the current profile of the area with projections of changes in land use for urban purposes. Two alternatives were proposed in these perspectives, one for preservation and the other for occupation, in accordance with guidelines already defined by the city’s Master Plan. The preservation scenario for the area was based on the analysis of environmental vulnerability to soil loss and the environmental conflict generated by potential urbanization, which proved to be significant and therefore a risk to water sources. On the other hand, the occupation scenario compared the infiltration capacity of the area with the current and urbanized land use, aiming for a land partition and occupation that would closely match the current infiltration capacity, in order to reduce some of the impact on water resources.